A quasi-resonant soft switching 48-pulse PWM inverter with closed loop current control for the realization of Static Synchronous Series Compensator (SSSC) - Ustun, Taha Selim; Mekhilef, Saad (American-Eurasian Network for Scientific Information, Jordan, 2009)
This paper discusses a 48-pulse H-bridge PWM inverter which utilizes a quasi-resonant topology that is comprised of a clamping circuit and a resonant circuit, in order to achieve soft switching. The use of a multi-pulse inverter increases the quality of the output whereas the implementation of soft switching technique increases the overall efficiency of the inverter by decreasing switching losses that reach considerable values with the abundant number of switches and a switching frequency of the order of KHz. Furthermore, in order to be able to respond load variations a feedback loop is constructed with a PI controller to realize closed loop current control. This system is aimed to be a building block for FACTS devices such as Static Synchronous Series Compensator (SSSC). The motivation of designing a more efficient and dynamic inverter with high power quality is to construct more efficient and effective FACTS devices.